Design of a Security Toolbox: A Framework To Mitigate The Risks of Cyberspace - Farelo, Nuno Miguel De Almeida (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management